Efektifitas Penggunaan Model Contextual Teaching And Learning Terhadap Keterampilan Menulis Pantun - Yoelandieta Adelina Said (LPPM Universitas PGRI Adi Buana, 2022)
The use of relevant methods, strategies and approaches in learning is needed, including the use of contextual teaching and learning (CTL) learning models in Indonesian subjects in improving the poetry writing skills and the fifth grade students’. The use of contextual teaching and learning (CTL) learning has the potential to develop the realm of process knowledge and skills and develop students’ attitudes, values and creativity in solving problems related to their daily lives, through interaction with fellow friends and also developing social skills. Barriers to learning through contextual models in writing poetry include students having difficulty in composing sentences in rows of lines in the form of addition and contents that match the theme, in group work only dominated by students who have higher potential writing skills, students are less willing to express opinions in response to reading rhymes and poems.